Analisis Kesesuaian Kompetensi Lulusan dengan Kebutuhan Dunia Kerja: Studi pada Lulusan Program Studi Tadris Bahasa Indonesia Universitas Islam Negeri Sumatera Utara - Indra Rasyid Julianto; Anugerah Agung Pohan (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
The alignment between graduate competencies and labor market requirements is an important indicator of higher education quality. This study examines the relevance of competencies possessed by graduates of the Indonesian Language Education Program (Tadris Bahasa Indonesia) at the State Islamic University of North Sumatera (UINSU) from the perspectives of alumni and graduate employers. A descriptive qualitative approach was employed, supported by quantitative data from tracer studies and employer satisfaction surveys. Data were collected through questionnaires, in-depth interviews, and document analysis involving alumni and five employers from educational institutions. The findings indicate a strong alignment between graduate competencies and workplace demands. The graduate employment rate reached 86.6%, with 93.3% of employed alumni working in the education sector. Employer satisfaction was highest in professional ethics (76.7% rated very good), educational expertise (70.0%), communication skills (66.7%), self-development competence (66.7%), information technology skills (63.3%), and teamwork and collaboration abilities (63.3%). Interview findings further revealed that graduates possess strong pedagogical, professional, social, and personal competencies. However, improvements are needed in foreign language proficiency, innovative teaching practices, digital literacy, and technology-enhanced learning development. The study recommends strengthening the Outcome-Based Education (OBE) curriculum and integrating twenty-first-century competencies to enhance graduate competitiveness and professional readiness.